Review of maxillary molar distalising appliances with palatal anchorage on miniimplants - Sanecka, Małgorzata; Becker, Katarzyna; Greń, Anna; Świerk, Mariusz (Forum Ortodontyczne / Orthodontic Forum, 2018)
Maxillary molar distalisation is one of treatment methods for patients with Angle class II. Intraoral appliances supported by patient’s own teeth inevitably lead to loss of anchorage. Mini-implants are additionally used to reduce this side effect. The area of the hard palate is the best anatomical place to attach mini-implants, and it provides the lowest risk of complications. Aim. To present issues associated with appliances used for maxillary molar distalisation that are based on bone anchorage in the hard palate region. Material and methods. The literature review using the PubMed database and the Polish Medical Bibliography with the following key words: molar distalisation, orthodontic miniimplants, skeletal anchorage. 37 positions from the years 1996–2018 were selected and analysed. Results. As a result of the literature review, 37 articles describing nine distalisation appliances modelled on three basic constructions: Pendulum, Distal Jet and Keles Slider, and the MCPP appliance were identified. Summary. Distalising appliances supported by palatal mini-implants do not lead to loss of anchorage in the anterior segment. At the stage of anterior teeth retraction they can be used for stabilisation of the distalised segment. They are less visible compared to extraoral appliances or those placed on the external side of the dental arch. They can be used simultaneously with fixed braces or during preparation for subsequent therapy with fixed braces. Depending on the design, they are not free of the side effects typical of the prototypes they originate from, i.e. rotation and inclination of molars. The most parallel distal movement of teeth is made possible by appliances whose force acts at the height of the CR (centre of resistance) of teeth being moved. (Sanecka M, Becker K, Greń A, Świerk M. Review of maxillary molar distalising appliances with palatal anchorage on mini-implants. Orthod Forum 2018; 14: 296-308).